Pemanfaatan Eco Enzym dan Pupuk P Terhadap Pertumbuhan dan Nodulasi Mucuna bracteata - Reza Andhika; Pauliz Budi Hastuti; Ryan Firman Syah (Politeknik Negeri Cilacap, 2023)
The research was conducted at Kebun Pendidikan dan Penelitian (KP 2) of the Yogyakarta Stiper Agricultural Institute located in Wedomartani Village, Depok District, Sleman Regency, D.I.Y with an altitude of 118 meters above sea level. The study began in February 2022 until May 2022. This research was carried out using a two-factor experimental method arranged in a Completely Randomized Design: the first factor was the concentration of eco enzym which consisted of 4 levels, namely, control (0 ml/liter), 1 ml/ liter, 2 ml/liter, and 3 ml/liter. The second factor was the dose of P fertilizer which consisted of 4 levels, namely: control (0 g/plant), 1.5 g/plant, 2.5 g/plant, and 3.5 g/plant. From these two factors, 4 x 4 = 16 treatment combinations were obtained, with each treatment being repeated 4 times so that the number of seeds obtained was 16 x 4 = 64 experimental plants. The research data were analyzed by analysis of variance (ANOVA) at the 5% level of significance. If there is a significant effect, the DMRT follow-up test is carried out at a significant level of 5%. The results showed that there was a significant interaction between the concentration of eco enzym treatment and the dose of P fertilizer on the root nodule weight parameter. The results showed that the combination treatment with eco enzym concentration of 3 ml/liter and P fertilizer dose of 1.5 gram/plant gave the best root nodule weight of Mucuna bracteata. The concentration of eco enzym and the dose of P fertilizer had the same effect on the growth of Mucuna bracteata.